2010
DOI: 10.1007/s10592-010-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic analysis of nuclear and mtDNA supports subspecies designations in the ostrich (Struthio camelus)

Abstract: We investigated the phylogeography and subspecies classification of the ostrich (Struthio camelus) by assessing patterns of variation in mitochondrial DNA control region (mtDNA-CR) sequence and across fourteen nuclear microsatellite loci. The current consensus taxonomy of S. camelus names five subspecies based on morphology, geographic range, mtDNA restriction fragment length polymorphism and mtDNA-CR sequence analysis: S. c. camelus, S. c. syriacus, S. c. molybdephanes, S. c. massaicus and S. c. australis. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…Similar conclusions were also reached in plants (e.g., shea tree: [110]; giant lobelia: [111]; coffee tree: [112]), insects (e.g., maize stalk borer: [113]), reptiles (e.g., puff adder: [114]; Southern rock agama: [115]) and birds (e.g., starred robin: [116]; ostrich: [117]). Zoogeographic barriers to dispersal have also been pointed out in several species, including the Rift Valley (e.g., lion: [118]; giraffe: [100]; wildebeest: [102]; waterbuck: [105]; bushbuck: [107]; maize stalk borer: [113]; giant lobelia: [111]) and great rivers (e.g., [95]).…”
Section: Discussionsupporting
confidence: 59%
“…Similar conclusions were also reached in plants (e.g., shea tree: [110]; giant lobelia: [111]; coffee tree: [112]), insects (e.g., maize stalk borer: [113]), reptiles (e.g., puff adder: [114]; Southern rock agama: [115]) and birds (e.g., starred robin: [116]; ostrich: [117]). Zoogeographic barriers to dispersal have also been pointed out in several species, including the Rift Valley (e.g., lion: [118]; giraffe: [100]; wildebeest: [102]; waterbuck: [105]; bushbuck: [107]; maize stalk borer: [113]; giant lobelia: [111]) and great rivers (e.g., [95]).…”
Section: Discussionsupporting
confidence: 59%
“…lineages were established during the late Pleistocene, between 60 000 and 13 000 years ago. Consistent with this, Taylor et al (2009) suggested that two lineages (Clade 1.1 and 2.1 in our analyses) underwent population expansion 12 956-3 360 y BP and 59 434-14 726 y BP, respectively, possibly associated with expansion from Pleistocene glacial refugia, a process shown to be influential in shaping patterns of genetic diversification among different taxa (Matthee & Robinson 1997;Hewitt 2000;Flagstad et al 2001;Muwanika et al 2003;Hewitt 2004;Anthony et al 2007;Brown et al 2007;Voelker et al 2010;Miller et al 2011).…”
Section: Discussionsupporting
confidence: 77%
“…The value is comparable to, or perhaps slightly higher, than heterozygosity estimates of ostrich ( Struthio camelus ) subspecies (average H E ranged from 0.30 to 0.71), which appears to be the only other ratite that has been studied with microsatellite analyses [56]. The level of genetic diversity we recorded for Dinornis , combined with the discrimination power documented in the ‘Probability of Identity’ analysis, suggest that these six markers a highly informative and suitable for population genetic studies of moa.…”
Section: Discussionmentioning
confidence: 52%